Absolute immature platelet count dynamics in diagnosing and monitoring the clinical course of thrombotic thrombocytopenic purpura. Issue 4 (5th November 2014) - Hong, Hong; Xiao, Wenbin; Stempak, Lisa M.; Sandhaus, Linda M.; Maitta, Robert W.
<x xml:space="preserve">Abstract</x> Background Thrombotic thrombocytopenic purpura (TTP) is a life‐threatening diagnosis requiring prompt initiation of therapeutic plasma exchange (TPE). Measurement of immature platelet (PLT) fraction (%‐IPF) differentiates PLT consumption or destruction from hypoproduction. Study Design and Method Our study evaluated %‐IPF changes over the course of TTP treated with TPE and as a measure of treatment efficacy. Eleven idiopathic TTP patients, two human immunodeficiency virus (HIV)‐associated TTP patients, and five non‐TTP patients with thrombocytopenia were enrolled into our study. All patients were treated with TPE and had ADAMTS13 activity measured. Results All idiopathic TTP patients had a significantly increased %‐IPF and decreased absolute immature PLT count (A‐IPC) and PLT count at presentation. An A‐IPC value of less than 5 × 109/L at presentation has 84.6% sensitivity, 80% specificity, and 91.7% positive predictive value for diagnosing TTP. A concurrent steady decline in %‐IPF and increased PLT counts toward normal was observed in TTP patients undergoing TPE. The A‐IPC, however, showed an increase and decrease curve that was not seen in the two HIV‐associated TTP patients with no response to TPE and the five non‐TTP patients. More importantly, reaching an A‐IPC ratio of 3 compared to baseline value during TPE can readily differentiate idiopathic TTP from the other two groups and is correlated with good clinical responses to TPE. An abrupt increase of A‐IPC during TPE was also noted in a TTP patient who relapsed 3 days before PLT count decrease. A‐IPC is positively correlated with ADAMTS13 activity at presentation but negatively correlated with ADAMTS13 activity during recovery. Conclusion A‐IPC should be routinely analyzed for diagnosing and monitoring TTP patients.